The Effectiveness of Nature of Science-Based Learning Programs to Stimulate Complex Problem-Solving in Global Warming - Laili Fauziah; Kartini Herlina; Doni Andra; Abdurrahman Abdurrahman (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
This study aims to measure students' complex problem solving on the concept of global warming. This study used a quasi-experimental design with nonequivalent control group design. The research subjects were 52 grade 11 high school students in Pesawaran District using a purposive sampling technique. This study uses eight essay questions as complex problem-solving instruments with six skill indicators, namely 1) articulating the problem, 2) identifying the desired result, 3) brainstorming creative options, 4) analyzing and choosing the best option, 5) developing an action plan that will achieve the result desired end 6) establish a plan of action and adapt as needed. The results showed that there was an effect of learning using the nature of science on students' complex problem solving with an increase of 0.75 in the high category in the experimental class compared to the control class with an increase of 0.35 in the medium category.